PENINGKATAN PENGETAHUAN CARA MENYUSUN MENU SEIMBANG PADA ANAK USIA SEKOLAH DENGAN METODE DEMONSTRASI - Erika Dewi Noorratri; Ari Septi Mei Leni (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2017)
Background : In this modern era, the need for is balanced nutrition and healthy food is not too important anymore. The main reason to eat quickly and look for food that also presented quickly without is seeing the nutrient content. In Indonesia, the Nutrition Adequacy Rate is still high (40.6%) of the population who consume foods with nutritional value below 70%, and are mostly found in school-aged children (41.2%). School-aged children can be at risk in nutrition problems. This can be due to the daily diet and the child's growth period. The target and outcome is 100% of the extension participants consisting of 4th grade students of SDN 2 Kerten Surakarta can improve their knowledge and understand about how to choose healthy snacks and able to prepare a balanced menu. Method of implementation: lectures and demonstrations. Result: students and students can mention the definition of healthy snacks, healthy snack benefits, unhealthy snack characteristics, healthy and unhealthy snacks, the impact of unhealthy snacks and can prepare a balanced menu. Conclusion: Students know about how to choose healthy snacks and able to mention healthy food, and able to arrange a balanced menu.